ĐÁNH GIÁ CHUYỂN ĐỘNG HIỆN ĐẠI ĐỚI ĐỨT GÃY LAI CHÂU - ĐIỆN BIÊN SỬ DỤNG CHUỖI SỐ LIỆU ĐO GPS 2002 - 2010 - Dương, Nguyễn Ánh; KIMATA, FUMIAKI; Tô, Trần` Đình; Xuyên, Nguyễn Đình; Nguyên, Phạm Đình; Hải, Vy Quốc; Công, Dương Chí (Vietnam Journal of Earth Sciences, 2012)
Contemporary horizontal movement estimation for Lai Chau - Dien Bien fault inferred from repeated GPS measurements in 2002 - 2010The article presents the result of the contemporary horizontal movement estimation for Lai Chau - Dien Bien fault derived from repeated GPS measuments from 2002 to 2010 using Bernese GPS Software version 5.0 (Bernese 5.0). In ITRF2000 reference frame, the measurement data of 06 IGS stations and 04 local GPS stations distributed both sides along the fault are used in processing. The result shows that: (1) the absolute horizontal velocity of the fault area wherethe local stations are located is about 34.6mm/year for east-southeastward movement; (2) the left-lateral slip rate isabout 2.3 mm/year; and (3) the opening speed of the fault is about 1mm/year. The results revealed in this study are consistent with other geo-tectonic studies on: (1) the opening-left-lateral slip of the fault system concerning with the normal movement; and (2) the left-lateral slip rate being larger at the southern part than at the northern part of the fault.